-28+6n=-2n+4(1+6n)

Simple and best practice solution for -28+6n=-2n+4(1+6n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -28+6n=-2n+4(1+6n) equation:



-28+6n=-2n+4(1+6n)
We move all terms to the left:
-28+6n-(-2n+4(1+6n))=0
We add all the numbers together, and all the variables
6n-(-2n+4(6n+1))-28=0
We calculate terms in parentheses: -(-2n+4(6n+1)), so:
-2n+4(6n+1)
We multiply parentheses
-2n+24n+4
We add all the numbers together, and all the variables
22n+4
Back to the equation:
-(22n+4)
We get rid of parentheses
6n-22n-4-28=0
We add all the numbers together, and all the variables
-16n-32=0
We move all terms containing n to the left, all other terms to the right
-16n=32
n=32/-16
n=-2

See similar equations:

| 3h+22=5h+6 | | (4b=b7 | | x+1,2=x-1,2 | | 3.50x+10=66 | | 4/5(3k-2)=5/4(2k-3) | | (1.09^x)=2 | | -179=-16h | | −13=−3u+10 | | -6(x-4)=4x-6 | | -(6+x)+3-5x=-15 | | 5^4x+3=35 | | x-5^7/8=16^5/8 | | 2n-6-4=n5 | | –(g+13)=–20 | | 24/30=n/5 | | 6x=77-5x | | 6x=77-5x | | 9j-8=12 | | x+4.5=19 | | 8(4s+7)=152 | | 8(4s+7)=152 | | x/38=14/28 | | 6.1(x−2)+x=51.7. | | x+133=172 | | 8w-3=1 | | 2.x+11=15 | | 2(4x-16)=8 | | 8b-2=38 | | 3/4n+8=28 | | -4x+7x+8=2x-5 | | 21w=-79 | | 1.5z-2=10 |

Equations solver categories